Functional characterization of the mutations in Pepper mild mottle virus overcoming tomato tm‐1‐mediated resistance. (19th January 2014) - Mizumoto, Hiroyuki; Morikawa, Yukino; Ishibashi, Kazuhiro; Kimura, Kentaro; Matsumoto, Kohei; Tokunaga, Masayuki; Kiba, Akinori; Ishikawa, Masayuki; Okuno, Tetsuro; Hikichi, Yasufumi
Summary In tomato plants, Pepper mild mottle virus (PMMoV) cannot replicate because the tm‐1 protein inhibits RNA replication. The resistance of tomato plants to PMMoV remains durable both in the field and under laboratory conditions. In this study, we constructed several mutant PMMoVs and analysed their abilities to replicate in tomato protoplasts and plants. We found that two mutants, PMMoV‐899R, F976Y and PMMoV‐899R, F976Y, D1098N, were able to replicate in tomato protoplasts, but only PMMoV‐899R, F976Y, D1098N was able to multiply in tomato plants. Further analysis showed that the D1098N mutation of the replication proteins weakened the inhibitory effect of the tm‐1 protein and enhanced the replication efficiency of PMMoV‐899R, F976Y, D1098N. We also observed that the infectivity of the viruses decreased in the order wild‐type PMMoV > PMMoV‐899R, F976Y > PMMoV‐899R, F976Y, D1098N in original host plants, pepper and tobacco plants. On the contrary, the single mutation D1098N abolished PMMoV replication in tobacco protoplasts. On the basis of these observations, it is likely that the deleterious side‐effects of mutations in replication proteins prevent the emergence of PMMoV mutants that can overcome tm‐1‐mediated resistance.